Mislocalisation of hephaestin, a multicopper ferroxidase involved in basolateral intestinal iron transport, in the sex linked anaemia mouse. Issue 2 (14th January 2004) - Kuo, Y M; Su, T; Chen, H; Attieh, Z; Syed, B A; McKie, A T; Anderson, G J; Gitschier, J; Vulpe, C D
Abstract : Background: Hephaestin is a multicopper ferroxidase required for basolateral transport of iron from enterocytes. Sex linked anaemia ( sla ) mice have a defect in the release of iron from intestinal enterocytes into the circulation due to an interstitial deletion in the hephaestin gene ( heph ). Results: We have demonstrated that hephaestin is primarily localised to a supranuclear compartment in both intestinal enterocytes and in cultured cells. In normal intestinal enterocytes, hephaestin was also present on the basolateral surface. In sla mice, hephaestin was present only in the supranuclear compartment. In contrast, the iron permease Ireg1 localised to the basolateral membrane in both control and sla mice. Conclusion: We suggest that mislocalisation of hephaestin likely contributes to the functional defect in sla intestinal epithelium.